A distributed location-aware routing architecture for P2P massively multiplayer online games - Ratti, Saurabh (University of Ottawa (Canada), 2010)
Populations in contemporary Massively Multiplayer Online Games (MMOG) continue to grow, a trend that current client-server architectures are hard pressed to sustain. Application of peer-to-peer concepts and technologies to the domain of MMOG communications can address the issues of scalability and single points of failure associated with the client-server model. A proposed system takes an existing peer-to-peer network overlay as a foundation for peer connection management, and adapts it to have location-awareness by applying the Hilbert Space-Filling Curve. The new routing architecture's location awareness is done with respect to the virtual environment, in order to achieve area-of-interest updates to interested peers with the latency of a single hop. This is done in manner that is fully distributed, thus sharing the work load as evenly as possible across peers without requiring centralized servers. This thesis reviews existing approaches, details the proposed system, and finally presents a proof-of-concept and associated evaluations.
Keywords: Engineering, Electronics and Electrical.